2020
DOI: 10.1002/mp.14200
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of 0.35 T magnetic resonance imaging radiomic features in stereotactic ablative body radiotherapy of pancreatic cancer: A pilot study

Abstract: The aim of this study was to evaluate the potential and feasibility of radiomic features extracted from low field strength (0.35 T) magnetic resonance images (MRIs) in predicting treatment response for patients with pancreatic cancer undergoing stereotactic body radiotherapy (SBRT). Methods: Twenty patients with unresected, non-metastatic pancreatic ductal adenocarcinoma (PDAC) were enrolled, all of whom received neoadjuvant chemotherapy followed by five-fraction MR-guided SBRT with a radiation dose range of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Previous reports showed that radiomics may potentially be used to quantify image textures in MRgRT data, and relate them to outcome in pancreatic [ 12 ] and rectal cancers [ 10 , 11 ] both in static and delta radiomic setting. Given the large number of features tested in small patient cohorts, as well as lack of image normalization, the results presented will require further validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that radiomics may potentially be used to quantify image textures in MRgRT data, and relate them to outcome in pancreatic [ 12 ] and rectal cancers [ 10 , 11 ] both in static and delta radiomic setting. Given the large number of features tested in small patient cohorts, as well as lack of image normalization, the results presented will require further validation.…”
Section: Discussionmentioning
confidence: 99%
“…In early proof-of-concept MRgRT radiomic studies, Boldrini et al [ 10 ] considered changes in extracted features using ratios pre- to post-treatment in 16 rectal cancer patients treated on a 0.35T MRgRT system showing promise for response correlation, later they followed up with another study in pancreatic cancer [ 11 ]. Simpson et al [ 12 ] looked at static, absolute values of radiomic features derived from 0.35T MRgRT scans for response prediction in 20 pancreatic cancer patients. With the increasing interest and promise in the field, there is an unmet need for establishing a robust MRgRT image quantification framework to extract the informational content of the imaging data and ensure reproducibility and reliability of extracted features.…”
Section: Introductionmentioning
confidence: 99%
“…As regards the Delta Radiomics MR-based models, the only experience to the best of our knowledge is represented by the study of Simpson et al, who showed how the delta approach on 0.35 T MR images may have a promising role in tumour response prediction of pancreatic cancer patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…Precise localization of the tumor and nearby organs at risk in real time has allowed for safe tumor dose escalation on hybrid MRI/RT machines [70]. In addition, on-board MRIgRT holds promise for improving [71] and pancreatic cancer [72]. Future studies will determine whether radiomics analysis of daily images from MRIgRT can similarly add prognostic value to prostate cancer treatment.…”
Section: Mri-guided Radiotherapymentioning
confidence: 99%